Going Out by Going In: Business Model Innovation with Chinese Characteristics. (17th March 2017) - Meyer, Marshall W.
Abstract : A radical model of "going out by going in" is proposed. Conventionally, firms enter overseas markets by selling and ultimately investing—this is "going out." Here, I argue that firms in emerging markets can draw revenues from overseas by penetrating previously inaccessible domestic markets and then renting their distribution and service channels to foreign competitors—this is "going out by going in." Further, firms in emerging markets can combine knowledge platforms with distribution and service platforms to create markets for innovative products and, again, rent these platforms to overseas competitors. Two cases, both from the Haier Group, are on point: Haier's Integrated Channel Services business targeting rural markets, and the Haier "water box" project aimed at supplying potable water to households throughout China. © 2017 Wiley Periodicals, Inc .